Bauran Pemasaran Bibit Anggur di Kebun Anggur Firizco Menggunakan Analytical Hierarchy Process (AHP) - Suci Yulianti; Erna Rachmawati (Universitas Galuh, 2026)
Nursery is the initial stage that determines the success of the horticultural agribusiness system, because seed quality affects agricultural productivity and sustainability. As public interest in high-value horticultural commodities increases, grape nurseries have greater market opportunities. Firizco Grape Garden is one of the grape seedling businesses that applies the 7P marketing mix strategy in marketing grape seedlings. This study aims to describe the application of the 7P marketing mix and determine the priority of alternative marketing strategies to increase the sales volume of grape seedlings at Firizco Grape Garden. The research method used is qualitative descriptive with the Analytical Hierarchy Process (AHP) as an analytical tool to determine the level of importance of each criterion and alternative marketing strategy, so as to obtain the marketing strategy that is most suitable for the conditions at Firizco Vineyard. Data collection was carried out through interviews, questionnaires, observations, and documentation involving respondents from within Firizco Vineyard. The analysis shows that the people component, which includes owners, managers, and employees directly involved in the production, service, and marketing of grape seedlings, has the highest priority, with strategies to improve product quality and technical services as the main alternative strategies to support increased sales of grape seedlings.